2023
DOI: 10.56578/josa010202
|View full text |Cite
|
Sign up to set email alerts
|

Application of Extended Fuzzy ISOCOV Methodology in Nanomaterial Selection Based on Performance Measures

Abstract: The prevalence of decision-making methodologies catering to quantitative attributes considerably overshadows those designed for qualitative attributes. This study seeks to address this gap by extending the traditional Ideal Solutions with Constraint on Values (ISOCOV) method to a fuzzy environment, thereby enhancing its capability to handle optimal decision-making based on qualitative attributes. In this improved method, α-cut representations are employed for managing linguistic value constraints in performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Within this analysis, individual criteria weights will be varied by designated percentages, i.e., 30%, 60%, and 90%, while the weights of other criteria remain unaltered. This process serves to gauge the diminished importance of a given criterion within the final decision [69][70][71]. Given the existence of 15 auxiliary criteria, and with their weights adjusted threefold, 45 distinct scenarios are established.…”
Section: Resultsmentioning
confidence: 99%
“…Within this analysis, individual criteria weights will be varied by designated percentages, i.e., 30%, 60%, and 90%, while the weights of other criteria remain unaltered. This process serves to gauge the diminished importance of a given criterion within the final decision [69][70][71]. Given the existence of 15 auxiliary criteria, and with their weights adjusted threefold, 45 distinct scenarios are established.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, estimates are given in the form of good, bad, medium, etc. It is easier for people to say that something is good, very good, or excellent than to evaluate it with numerical ratings using, e.g., a grade of 4 or 5 [41]. By using these values, this research is more adapted to human thinking.…”
Section: Methodology and Methodsmentioning
confidence: 99%
“…Thus, a fuzzy set that uses linguistic values was first formed [40] in order to employ imprecise information in decision making. Linguistic values are used in many studies and have shown their advantages and applicability [41,42]. Subsequently, a rough set enabling decision making in conditions of uncertainty with a reduced subjective influence from decision makers was created [43].…”
Section: Preliminariesmentioning
confidence: 99%
“…Wang and Chen [40] used a T-spherical fuzzy ELECTRE approach to select potential companies for extending the scope of a business. Some recent fuzzy MCDM works can be seen in the work of Badi et al [41], Martin and Edalatpanah [42], Puška and Stojanović [43], and Su et al [44]. However, fuzzy ELECTRE I has yet to be applied to select demand forecasting methods for sustainable manufacturing.…”
Section: Fuzzy Electre Methodsmentioning
confidence: 99%